BUHARAK LAMPUNG SAIBATIN SEBAGAI PELESTARIAN BUDAYA LAMPUNG PESISIR - Atha Nabitha Salsabila; Serlia Maharani; Mulyanto Widodo; Rahmat Prayogi (Jurnal Manajemen Pendidikan, 2025)
This study aims to describe and analyze the Buharak tradition among the Lampung Saibatin community as a form of cultural preservation in the Lampung Pesisir region. Buharak is a wedding procession held after the marriage ceremony with the aim of introducing the couple to the community while affirming the honor of the family and social status in the Saibatin customary system. This study uses a descriptive qualitative method with in-depth interview techniques, participatory observation, and documentation studies of traditional leaders, ritual performers, and coastal communities. Data analysis is carried out through a thematic approach with stages of reduction, categorization, and interpretation of meaning. The results show that Buharak has three main functions: as a social glue that strengthens community solidarity and mutual cooperation (sakai sambayan); as a marker of status and customary legitimacy that reflects the hierarchical social structure of the Saibatin community; and as an arena for negotiating modernity, where the younger generation and religious leaders adapt traditional practices to align with Islamic norms and current socio-economic conditions. This adaptation is evident in the simplification of the duration of the procession, reduction of costs, integration of religious elements, and digital documentation that expands the scope of cultural preservation.